Characterization of the UK anthrax vaccine and human immunogenicity. Issue 3 (4th March 2021) - Modi, Tapasvi; Gervais, David; Smith, Stuart; Miller, Julie; Subramaniam, Shaan; Thalassinos, Konstantinos; Shepherd, Adrian
ABSTRACT: The manufacture of the UK Anthrax vaccine (AVP) focuses on the production of Protective Antigen (PA) from the Bacillus anthracis Sterne strain. Although used for decades, several of AVP's fundamental properties are poorly understood, including its exact composition, the extent to which proteins other than PA may contribute to protection, and whether the degree of protection varies between individuals. This study involved three innovative investigations. Firstly, the composition of AVP was analyzed using liquid chromatography tandem mass-spectrometry (LC-MS/MS), requiring the development of a novel desorption method for releasing B. anthracis proteins from the vaccine's aluminum-containing adjuvant. Secondly, computational MHC-binding predictions using NetMHCIIpan were made for the eight most abundant proteins of AVP, for the commonest HLA alleles in multiple ethnic groups, and for multiple B. anthracis strains. Thirdly, antibody levels and toxin neutralizing antibody (TNA) levels were measured in sera from AVP human vaccinees for both PA and Lethal Factor (LF). It was demonstrated that AVP is composed of at least 138 B. anthracis proteins, including PA (65%), LF (8%) and Edema Factor (EF) (3%), using LC-MS/MS. NetMHCIIpan predicted that peptides from all eight abundant proteins are likely to be presented to T cells, a pre-requisite for protection; however, the number of such peptides varied considerably between different HLA alleles. These analyses highlight two important properties of the AVP vaccine that have not been established previously. Firstly, the effectiveness of AVP within humans may not depend on PA alone; there is compelling evidence to suggest that LF has a protective role, with computational predictions suggesting that additional proteins may be important for individuals with specific HLA allele combinations. Secondly, in spite of differences in the sequences of key antigenic proteins from different B. anthracis strains, these are unlikely to affect the cross-strain protection afforded by AVP.